Analysis of the information security management in Czech Republic - Svoboda, Tomáš; Horálek, Josef (American Scientific Publishers, 2018)
The aim of this article is to introduce an implementation of information security management into organizations in Czech Republic, using the ČSN/ EN ISO/IEC 27001 standard. Information security, on which a high demand is focused nowadays, is introduced firstly. Next, the evolution of information security standards is described in detail. Based on the theoretical background, the research about implementation of information security standards in Czech Republic is conducted, by using a questionnaire survey as a research method. The results of this survey, which reflect responses from more than 30 organizations, are presented in detail.
Analýza řízení informační bezpečnosti v České republice
Keywords: Certification; Standards; Information; Security; Survey